2006
DOI: 10.1177/1090198105282410
|View full text |Cite
|
Sign up to set email alerts
|

Community Agency Survey Formative Research Results From the TAAG Study

Abstract: School and community agency collaboration can potentially increase physical activity opportunities for youth. Few studies have examined the role of community agencies in promoting physical activity, much less in collaboration with schools. This article describes formative research data collection from community agencies to inform the development of the Trial of Activity for Adolescent Girls (TAAG) intervention to provide out-of-school physical activity programs for girls. The community agency survey is designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…The TAAG Community Agency Survey, a study designed to assess agency capacity to provide physical activity programs for girls in potential TAAG schools, found that basketball programs at community centers were the most commonly offered and the most popular among girls. 22 Unlike previous studies, which also identify a link between perceived measures of facilities and physical activity in adolescents, 1,23,24 this study demonstrates that the higher levels of nonschool MW-MVPA associated with greater perception of recreational resources are independent of the objective presence of these same facilities. Given this finding, the public health advocates should find ways to improve the perception of recreational sites in the community.…”
Section: Commentcontrasting
confidence: 51%
See 1 more Smart Citation
“…The TAAG Community Agency Survey, a study designed to assess agency capacity to provide physical activity programs for girls in potential TAAG schools, found that basketball programs at community centers were the most commonly offered and the most popular among girls. 22 Unlike previous studies, which also identify a link between perceived measures of facilities and physical activity in adolescents, 1,23,24 this study demonstrates that the higher levels of nonschool MW-MVPA associated with greater perception of recreational resources are independent of the objective presence of these same facilities. Given this finding, the public health advocates should find ways to improve the perception of recreational sites in the community.…”
Section: Commentcontrasting
confidence: 51%
“…In light of the fact that girls at five out of six TAAG sites most often used transportation by car to get to their after-school activities 22 and that 69% of all trips made by children aged 5 to 15 are by private vehicle, 25 it is not surprising that family transportation is one of the principal mechanisms through which girls perceive their environment. Thus, public officials would do well to not only promote recreational programs and opportunities, but also to organize transportation for young people or organize more school-based opportunities for girls to be active.…”
Section: Commentmentioning
confidence: 99%
“…This article focuses on development of the PE component of the intervention through the use of formative research findings and summarizes how school policies and practices aligned with national standards for PE. The three other intervention components and the research that informed their development are described elsewhere in this special issue (Saunders & Moody, 2006;Staten, Birnbaum, Jobe, & Elder, 2006;Vu, Murrie, Gonzalez, & Jobe, 2006;Young et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The results of formative research are presented in detail in other work published in this supplement Moe et al, 2006;Saunders & Moody, 2006;Staten, Birnbaum, Jobe, & Elder, 2006;Vu et al, 2006). There were, however, some key findings that had overarching implications for intervention planning.…”
Section: Formative Research Resultsmentioning
confidence: 99%